Clinical Application of Echocardiography in Evaluating Left Ventricular Diastolic Function in Patients with Acute Pulmonary Embolism - Shiyang Qin (Computational and Mathematical Methods in Medicine, 2022)
Objective. To explore the clinical application of echocardiography in assessing left ventricular diastolic function in patients with acute pulmonary embolism (APE). Methods. About 90 patients with APE treated in our hospital from March 2016 to March 2019 were enrolled as the study group. The enrolled patients were assigned into three groups in accordance with the risk stratification of APE, with 30 patients in each group, including high-risk group, medium-risk group, and low-risk group. Approximately 90 healthy persons who underwent physical examination in the same period were enrolled as the control group. The two groups were used to analyze the clinical value of echocardiography in evaluating left ventricular diastolic function in patients with APE and to explore the correlation between left ventricular diastolic function and different risk stratification of APE. Results. First of all, we compared the side values of echocardiography. Compared to the control group, right ventricular end-diastolic diameter/left ventricular end-diastolic diameter (RVED/LVED) and pulmonary artery systolic pressure (PASP) in the study group were higher, while left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), left ventricular volume per stroke (LVSV), and left ventricular ejection fraction (LVEF) in the study group were lower (P<0.05). Secondly, we compared the echocardiographic side values of patients with different APE risk stratifications: (1) RVED/LVED, PASP: low‐risk group<medium‐risk group<high‐risk group; (2) LVEDV, LVESV, LVSV, LVEF: low‐risk group>medium‐risk group>high‐risk group (P<0.05). The routine echocardiographic findings of APE patients: M-type left ventricular wave group of pulmonary embolism (PE) indicated right ventricular enlargement and interventricular septum shifted to the left ventricle; short-axis section of PE artery indicated thrombosis at the opening of the right pulmonary artery (indicated by arrow); long-axis section of the left ventricle of PE indicated right ventricular enlargement (RV 3.5 cm, LV 3.9 cm); four-chamber view of PE indicated enlargement of the right atrium and the right ventricle, and interventricular septum shifted like left ventricle. In terms of mitral annulus displacement, early diastolic ESD and ELD in the study group were lower compared to those in the normal control group, while late diastolic ASD and ALD in the study group were higher compared to those in the normal control group (P<0.05). The results of Pearson correlation analysis indicated that there was a positive correlation between RVED/LVED, PASP, and APE risk stratification, while APE risk stratification was negatively correlated with LVEDV, LVESV, LVSV, and LVEF (P<0.05). Conclusion. Echocardiography attaches importance to the evaluation of left ventricular diastolic function in APE. The side value of echocardiography can sensitively reflect the changes of left ventricular diastolic function in APE. The predictive value in the diagnosis of APE is better than other traditional parameters of left ventricular diastolic function, especially in patients with different APE risk stratifications. There is a remarkable correlation between the changes of left ventricular diastolic function and different APE risk stratifications. Echocardiographic measurement can be employed to assess left ventricular diastolic function in APE, which can be developed in clinical treatment and prognosis evaluation to provide a new evaluation method.